Análise crítica do discurso da Terapia Comunitária Integrativa: linguagem, poder e efeitos terapêuticos de sentido. - Misici, Emidio Giuseppe Pinheiro (2022)
Introduction - This master´s dissertation intends to analyze, from the Critical Discourse Analysis (CDA) perspective, the practice known as Integrative Community Therapy (ICT), a mental health care procedure that helps participants sharing of affection using the spoken word. It connects traditional science with the appreciation of local knowledge and cultures and it is used in different parts of the world. Objective – To analyze Integrative Community Therapy (ICT) as a practice of embracing suffering and strengthen community ties from the perspective of Critical Discourse Analysis (CDA). Method - It consists of a qualitative exploratory method with a critical orientation, based on CDA, through two video transcriptions. The videos are available on the website https://www.cursosab.com/videos. The corpus is composed of two videos, two transcripts and the orientation text of the ICT procedures. The interpretation of the collected material fulfills the teachings of the CAD by Norman Fairclough (2003). Results - The ICT consists, as a discourse, in a variety of genres, whereas social, organized by genres, they seek to facilitate conversation and achieve the objective of embracing participants in an egalitarian way, with the attenuation of hierarchy. It is, however, possible to observe in the sessions, the reproduction of incorporated social roles and the manifestation of power in micro-relationships. As a Complementary Integrative Practice, it faces some challenges in its performance with regard to the public and space for action. Conclusion - TCI deals with social issues with a libertarian objective. It can be a space for identifying social problems and representing production of models of domination, and also their overcoming by the identification of these models.